2004
DOI: 10.1016/s1015-9584(09)60039-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Piperacillin/Tazobactam Versus Imipenem/Cilastatin in the Treatment of Patients with Intra-abdominal Infection

Abstract: These results suggest that the safety and efficacy of piperacillin/tazobactam administered every 8 hours are equivalent to those of imipenem/cilastatin administered every 6 hours for the treatment of intra-abdominal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 11 publications
1
31
0
1
Order By: Relevance
“…From this study, it was found that the isolates were mostly sensitive (89% -84%) to the drugs like amikacin, imipenem, cefoperazone-sulbactam followed by meropenem, ciprofloxacin, ceftazidime, ticarcillin-clavulanic acid (all in the range of 78% -74%) and lastly against ceftriaxonetazobactam and gentamicin (68%-63%). These pathogens showed high resistance to tetracycline, piperacillin, cefotaxime, azithromycin, oxacillin, mecilinam and gatifloxacin (approx 68% -47%) which were also reported by workers like Erasmo et al (2004), Sivanmaliappan and Sevanan (2011) and Hill et al (2005) showing resistance of this pathogen against piperacillin, ticarcillin and tetracycline, ceftazidime, co-trimoxazole and cefoperazone in various degrees. Javiya et al (2008) reported that drugs like ticarcillin, piperacillin or 3 rd generation cephalosporins viz.…”
Section: In-vitro Antibiotic Sensitivity Test (Ast) Ofsupporting
confidence: 67%
“…From this study, it was found that the isolates were mostly sensitive (89% -84%) to the drugs like amikacin, imipenem, cefoperazone-sulbactam followed by meropenem, ciprofloxacin, ceftazidime, ticarcillin-clavulanic acid (all in the range of 78% -74%) and lastly against ceftriaxonetazobactam and gentamicin (68%-63%). These pathogens showed high resistance to tetracycline, piperacillin, cefotaxime, azithromycin, oxacillin, mecilinam and gatifloxacin (approx 68% -47%) which were also reported by workers like Erasmo et al (2004), Sivanmaliappan and Sevanan (2011) and Hill et al (2005) showing resistance of this pathogen against piperacillin, ticarcillin and tetracycline, ceftazidime, co-trimoxazole and cefoperazone in various degrees. Javiya et al (2008) reported that drugs like ticarcillin, piperacillin or 3 rd generation cephalosporins viz.…”
Section: In-vitro Antibiotic Sensitivity Test (Ast) Ofsupporting
confidence: 67%
“…Contrary to this resistance rate in isolates was higher in our study (42%). In a previous study equivalent safety and efficacy of intravenous Piperacillin/tazobactam with intravenous imipenem/cilastatin was reported for intra-abdominal infections caused by Pseudomonas aeruginosa but presently resistance was different for both antibiotics which might be due to extensive usage of this combination in our hospitals as life saving antibiotics (Erasmo et al 2004). …”
Section: Discussionmentioning
confidence: 56%
“…Clinical outcome data of piperacillin-tazobactam versus comparators have been extensively reviewed elsewhere [72] and therefore will not be discussed in detail. Suffice to say, piperacillin-tazobactam has been shown to be as effective and safe as imipenem-cilastatin or doripenem for nosocomial pneumonia [73,74], as imipenem-cilastatin or ertapenem for complicated intra-abdominal infections [75][76][77][78], as meropenem, cefepime, ceftazidime, or piperacillin-tazobactam plus amikacin for febrile neutropenia [79][80][81][82], as ertapenem or imipenemcilastatin for diabetic foot infection [83,84], as ertapenem for complicated skin and soft tissue infections [85,86], and as ertapenem for acute pelvic infections [87]. Therefore, piperacillin-tazobactam has been recommended in various clinical guidelines for treatment of a wide range of infections [2-9].…”
Section: Clinical Outcome Datamentioning
confidence: 99%